2014
DOI: 10.1089/dna.2013.2333
|View full text |Cite
|
Sign up to set email alerts
|

FCGR3A158V/F Polymorphism and Response to Frontline R-CHOP Therapy in Diffuse Large B-Cell Lymphoma

Abstract: The influence of Fc gamma receptor IIIA (FCGR3A) 158V/F polymorphisms on the response to rituximab (R) plus CHOP (cyclophosphamide, doxorubicin, vincristine, prednisone; R-CHOP) therapy in diffuse large B-cell lymphoma (DLBCL) is uncertain. Thus, a retrospective study and a meta-analysis were performed to examine the possible correlation between FCGR3A 158V/F polymorphism and the response rate of R-CHOP regimen in patients with newly diagnosed DLBCL. The genotypes of FCGR3A 158V/F in 164 newly diagnosed DLBCL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 32 publications
0
13
0
1
Order By: Relevance
“…Despite this, several of these studies did show correlations with response suggesting that FccR are playing a role, but that larger studies may be needed to obtain significant data. Recently, Liu et al (22) carried out their own study and meta-analysis combining data from seven previous studies and although again they were able to show a trend toward significance for FccR SNP (relating to enhanced Fc affinity) and outcome, they were unable to demonstrate a statistically significant correlation. In their study, they modeled the number of patients that would be required to obtain sufficient power to show a correlation in rituximab responses in DLBCL, given the response rates observed overall and found that they would need 811 cases.…”
Section: Fccr Dependence Of Clinical Mabsmentioning
confidence: 96%
“…Despite this, several of these studies did show correlations with response suggesting that FccR are playing a role, but that larger studies may be needed to obtain significant data. Recently, Liu et al (22) carried out their own study and meta-analysis combining data from seven previous studies and although again they were able to show a trend toward significance for FccR SNP (relating to enhanced Fc affinity) and outcome, they were unable to demonstrate a statistically significant correlation. In their study, they modeled the number of patients that would be required to obtain sufficient power to show a correlation in rituximab responses in DLBCL, given the response rates observed overall and found that they would need 811 cases.…”
Section: Fccr Dependence Of Clinical Mabsmentioning
confidence: 96%
“…In small studies of follicular lymphoma, FCGR2A ‐131R and FCGR3A ‐158F homozygous individuals experienced reduced efficacy of rituximab, compared to 131H and 158V homozygotes, respectively although these data have not been replicated in all studies . A meta‐analysis of studies involving R‐CHOP therapy (rituximab plus cyclophosphamide, doxorubicin, vincristine, and prednisone chemotherapy) in diffuse large B‐cell lymphoma found no correlation between FCGR3A F158V genotype status and overall response rates; although FCGR3A ‐158F homozygotes experienced a statistically significant shorter progression‐free survival than other genotypes . Significant associations with the FCGR2A ‐131H and FCGR3A ‐158V alleles and responses to trastuzumab (anti‐human epidermal growth factor receptor 2; HER2) treatment were found in small studies of HER2‐positive breast cancer ; however, these data were not repeated in a large trial of >1000 patients .…”
Section: Fcγr Genetic Variation and Immunotherapymentioning
confidence: 99%
“…For trastuzumab, FcGR2A H/H and FcGR3A V/V are reported to be correlated with prolongation of progression-free survival (PFS) in metastatic breast cancer, FcGR2A H/H and FcGR3A V/V were reported to be correlated with pathological complete remission in the neo-adjuvant setting, and no obvious correlation was found between FcGR and overall survival in the adjuvant setting; thus, there is still no unified view [19][20][21][22] . Similarly, rituximab has been investigated for its effect on drug efficacy against follicular lymphoma and diffuse large B cell lymphoma (DLBCL), but there are no reports of statistically significant effects, except in the early 2000s [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] . As described above, FcGR SNPs and the ADCC activity of antibody drugs are clear in vitro, but their relationship with clinical efficacy is not clear.…”
Section: Goldgate Genotypingmentioning
confidence: 99%
“…FcgRIIIA polymorphism status may be predictive of survival in FL patients receiving treatments containing an anti-CD20 antibody but not treatment with chemotherapy alone Liu [37]…”
Section: Taqman Snp Assaymentioning
confidence: 99%